The Determinants of Tax Avoidance: Evidence from Indonesia’s Property and Real Estate Sector - Nabila Naila Shakira; Tituk Diah Widajantie (Politeknik Ganesha Medan, 2026)
This study aims to analyze the determinants influencing tax avoidance practices among property and real estate sector companies in Indonesia. The variables examined include profitability, leverage, capital intensity, and financial distress as factors presumed to affect corporate tax decision-making. The focus of this study is grounded in the importance of understanding how financial and operational characteristics of companies, particularly within a sector characterized by high asset intensity and long business cycles, may influence the tendency toward aggressive tax planning. This study employs a quantitative approach based on secondary data drawn from the annual reports of companies listed on the Indonesia Stock Exchange (IDX) over the observation period of 2022 to 2024. The sample consists of 34 companies selected through purposive sampling. Empirical analysis was conducted using multiple linear regression to examine the relationships among variables, with the aid of SPSS software version 27. The results indicate that profitability has a positive effect on tax avoidance, while capital intensity has a negative effect. Meanwhile, leverage and financial distress do not exhibit a significant influence on tax avoidance. These findings suggest that not all financial indicators serve as relevant predictors of tax avoidance in the property and real estate sector in Indonesia.